Assessing 'unnatural lusts': John Locke on the permissibility of male-male intimacy. Issue 1 (2nd January 2023) - Smith, Brian
ABSTRACT: This paper argues that Locke offers qualified support for male-male intimacy. While one can find denunciations of sodomy and 'debauchery' in his work, these claims are embedded in a natural and divine law framework that did not formally specify how to define much less morally characterize these actions. At the very least, Locke makes it difficult to strictly condemn sodomy or other homosexual acts as inherently immoral. This paper will explore three areas of interest: 1) Locke's Paraphrases of the Pauline epistles in which he argues that Paul's interest in sexuality concerns temple idolatry rather than a trans-generational sexual ethic; 2) the empirical terms in which he appears to reject the viability of sodomy and his interest in native sexual practices show that he tolerated alternative conjugal frameworks; and 3) the curious case of his own sexuality, the passionate letters he shared with close male friends suggest that sexual obligations to society were not permanent and that as one ages alternative forms of love may be permitted.